Media Permainan Matematika untuk Meningkatkan Minat Belajar Anak Usia 5-6 Tahun - Farah Ayu Maulidina; Sukiman Sukiman (Universitas Cokroaminoto Palopo, 2024)
This research aims to develop math game media suitable for children aged 5-6 years and to see their learning interest in math material. This research is a qualitative research with the ADDIE model development method. This research will only be conducted up to the product trial stage (limited trial) in the PAUD unit where the research is conducted, so the results obtained are still in the form of a prototype model. Based on the validation results from two material experts, the overall percentage of material feasibility in the game media is 89.84% with a very feasible category to use. While the results of validation from media experts, the overall percentage of media feasibility in game media is 93.18% so that the game media developed is very feasible to use. After the game media developed was deemed suitable for use, researchers began conducting limited trials with two classes of fifteen children each from group B at KB Mutiara Serat Bangsa. The total percentage of children's learning interest in class B1 obtained was 80.21% with a very interesting category and 75.42% in class B2 with an interesting category. So it can be concluded that the use of math game media developed in the limited trial stage is able to attract children's learning interest in math material. Digital games succeeded in increasing children's interest and enthusiasm in learning while helping them understand the subject matter better. Incorporating interactive games into early childhood education is a great way to create a learning environment that stimulates and encourages children's overall development.